Applicability analysis to evaluate credibility of an in silico thrombectomy procedure. (20th September 2021) - Luraghi, Giulia; Bridio, Sara; Miller, Claire; Hoekstra, Alfons; Rodriguez Matas, Jose Felix; Migliavacca, Francesco
Abstract: Intra-arterial thrombectomy is a minimally invasive procedure in which an obstructing thrombus (clot) is removed using a minimally-invasive device: a stent-retriever. The stent-retriever is first deployed, and then the thrombus is removed during stent-retriever retraction. This procedure can be simulated using a detailed computational model. However, to be useful for an in silico trial in a clinical setting, model credibility should be demonstrated. The aim of this work is to apply a credibility process for the validation phases to the thrombectomy procedure in order to deem it credible for use in an in silico trial. Validation evidence is proposed for the identified context of use and then used to build credibility to the numerical model. Applicability of the proposed model is justified and assessed using a rigorous step-by-step method based on the ASME V&V40 protocol.